Relevansi Prestasi Belajar Sebagai Prediktor Perilaku Empati Di SMA Negeri 5 Samarinda - Siti Murti; Heryanto Heryanto (Peneliti.net, 2020)
The purpose of this study is to analyze the relevance of behavior empathy with student achievement, so that its contribution to learning achievement is known. This research includes the type of verification research conducted through data collection in the field using survey methods. The unit of analysis was taken using a simple random sampling technique. Data was collected through observation, interviews, questionnaires, and documentation. This study consist two variables, namely empathy behavior as the dependent variable, and student learning achievement as the independent variable. The results of the study show that the student learning achievement has a positive effect on reasoning empathy behavior significantly. The correlation between empathy behavior reasoning and student achievement is 0.729 (the degree of relationship is strong). This means that students' empathy behavior reasoning is 53.14% determined by learning achievement factors, and 46.86% is determined by other factors.